2016
DOI: 10.1016/j.vacuum.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Critical angles in DC magnetron glad thin films

Abstract: a b s t r a c tThe objective of this study is to examine the sudden drop in properties of aluminum, titanium and chromium thin films prepared by the glancing angle deposition method. The thin films were deposited by DC magnetron sputtering under identical deposition conditions. A substrate-holder with seven different orientations with respect to the target normal was used. The thickness and the column tilt angles (b) of the thin films were determined by scanning electron microscopy. The residual stress of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 60 publications
7
26
0
Order By: Relevance
“…This difference between ρ x and ρ y is once again related to the microstructure of W thin films. It was clearly demonstrated that GLAD deposition of columnar films with incident angles higher than 60 • (critical-like angle) produced significant structural and uniaxial anisotropy in the substrate plane induced by the shadowing effect [57]. Thus, an anisotropic distribution of the grain boundary potential barrier heights was formed in the direction of the incoming atoms (x-axis), especially at low argon sputtering pressure due to the high directional behavior of the particle flux.…”
Section: Electrical Resistivitymentioning
confidence: 99%
“…This difference between ρ x and ρ y is once again related to the microstructure of W thin films. It was clearly demonstrated that GLAD deposition of columnar films with incident angles higher than 60 • (critical-like angle) produced significant structural and uniaxial anisotropy in the substrate plane induced by the shadowing effect [57]. Thus, an anisotropic distribution of the grain boundary potential barrier heights was formed in the direction of the incoming atoms (x-axis), especially at low argon sputtering pressure due to the high directional behavior of the particle flux.…”
Section: Electrical Resistivitymentioning
confidence: 99%
“…However, studies on the stress evolution in thin films deposited at off-normal conditions remain scarce [8,59,60]. Siad et al [8] have reported a critical angle of α ~ 60° above which the absolute stress magnitude decreases for Al, Ti, and Cr films. They attributed this change to self-shadowing effect and decrease of average energy of incoming particles.…”
Section: Stress Evolutionmentioning
confidence: 99%
“…Most studies on films produced with obliquely incident vapor flux have concerned metals and oxides [4], which were primarily synthesized at low temperature and low deposited energy (typically by thermal and electron beam evaporation) to benefit from exacerbated shadowing effects [6]. Combining oblique angle geometries and sputter-deposition technique provides additional degree of freedom to adjust the film morphological features (porosity and column tilt angle) and stoichiometry by varying the deposition pressure or target power [7][8][9][10][11] and employing more than one material source [12][13][14][15]. However, studies on transition metal nitride (TMN) films produced at OAD or GLAD conditions remain relatively underexplored [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…From the initial conditions of sputtered atoms 11 , the particles trajectories are described individually. As a result, the software reports the energy and the incident angle 12,13 of atoms hitting a surface, as well the fraction of deposited atoms in any surface 14 , including the target 15 .…”
Section: Introductionmentioning
confidence: 99%